The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0271690
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin at moderately increased levels confers a neuroprotective effect in non-secreting pituitary macroadenomas

Abstract: Context Prolactin, a hormone synthesized by the anterior pituitary gland demonstrates promise as a neuroprotective agent, however, its role in humans and in vivo during injury is not fully understood. Objective To investigate whether elevated levels of prolactin attenuate injury to the retinal nerve fiber layer (RNFL) following compression of the optic chiasm in patients with a prolactin secreting pituitary macroadenoma (i.e., prolactinoma). Design setting and participants A retrospective cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has also been reported that PRL has complex stimulatory and regulatory effects on neural stem cell activity and may itself play a role in the recovery process associated with damage in the brain via signal transduction through PRLR [28]. PRL is also expected to be a neuroprotective agent, but its role in humans during hypoxia is not fully understood, and in vivo studies are lacking [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that PRL has complex stimulatory and regulatory effects on neural stem cell activity and may itself play a role in the recovery process associated with damage in the brain via signal transduction through PRLR [28]. PRL is also expected to be a neuroprotective agent, but its role in humans during hypoxia is not fully understood, and in vivo studies are lacking [29].…”
Section: Introductionmentioning
confidence: 99%